Estate Taxes, Life Insurance, and Small Business - Holtz-Eakin, Douglas; Phillips, John W. R.; Rosen, Harvey S. (The Review of Economics and Statistics, 2001)
Critics argue that the estate tax prevents the owners of family businesses from passing their enterprises to heirs because it is difficult to pay estate taxes without liquidating the business. Why don't owners purchase enough life insurance to meet their estate tax liabilities? We examine whether and how people use life insurance to deal with the estate tax. We find that, ceteris paribus, business owners purchase more life insurance than do other individuals. However, on the margin, their insurance purchases are less responsive to estate tax considerations, and they are less likely to have the wherewithal to meet estate tax liabilities out of liquid assets plus insurance.